Optimizing Character Education through Local Wisdom in Aceh: Approaches, Obstacles, and Solutions - Idris, M. Arif; Suroto, Suroto (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study examines the potential for enhancing character education in Aceh Province by integrating local wisdom, with the objective of gaining insight into the implementation process and the factors that may influence it. Qualitative methods, including interviews, observations, and documentation, were employed to identify key strategies, which included community socialisation, fostering positive habits, integrating local wisdom into curricula, implementing policies, and allocating financial resources. The presence of Taman Pendidikan Alquran (TPQ), taklim assemblies, dedicated teachers, regulations pertaining to local wisdom, Islamic law, historical and cultural coherence, and robust institutional coordination serve as key supporting factors. However, a number of challenges have been identified which impede effective implementation, including the location of Aceh on the border, the influence of diverse tribal cultures, the impact of external cultures, population mobility, environmental factors, the impact of the pandemic, and the lack of standardised curricula and resources.